It's time for Acting Up!. (January 2018) - Prichard, Craig; Benschop, Yvonne
All ranking journals, including critical ones such as Organization, regard a contribution to theory as the Holy Grail of academic writing. But it is a long way to a better world through theory alone. In this article, we discuss the challenges of making action and activism a feature of academic work and we introduce a new space in Organization, entitled Acting Up, for short papers that take up such a challenge.